Investigation on the effects of physical parameters of terahertz bow-tie photoconductive antennas to their performance: article / Ameerul Faisal Asmari - Asmari, Ameerul Faisal (2014)
The physical parameters of bow-tie photoconductive antenna is investigated, their effects and relationship with resonant frequency have been reviewed and discussed. The reference dimensions for 1 terahertz (THz) resonant frequency bow-tie photoconductive antenna has been used. Analysis has been done using data from the parameter sweep simulation result. The parameter chosen is dipole length, angles of tapered flare, gap length, gap width, substrate length, substrate width, substrate thickness and copper thickness. 10 dimension is taken for each parameter and their relationship to the resonant frequency is illustrated in graph. The simulation is done by using CST Studio Suite and plotted by Matlab software. From the analysis studied, the dipole length and gap length affect the resonant frequency but with uncertain characteristics. Other parameters also affect the resonant frequency but with predictable characteristics. Angle of tapered flare, gap width and copper thickness share almost the same pattern which is the resonant frequency gets higher as their dimension increased. Substrate width, substrate thickness and substrate length however gives difference characteristics which is the resonant frequency gets lower as their dimension increased. This study conclude that all the investigated parameter affect the resonant frequency of bow-tie photoconductive antenna.